Resilience and psychoanalysis: a systematic review - Malgarim, Bibiana Godoi; Santana, Márcia Rosane Moreira; Machado, Amanda Pacheco; Bastos, Andre Goettems; Freitas, Lúcia Helena (Psico, 2018)
The aim of this paper was to investigate the concept of resilience by studying texts published in the field of psychoanalysis (over a ten-year period). Through a systematic review of articles published between 2004 and 2014, using descriptors in Portuguese, Spanish and English. Five data bases were searched, namely Pubmed, Lilacs, Scielo, BVS Index Psi and PsycInfo. We gathered 280 published items, including articles, papers, reviews and other types of material. After exclusion criteria, 11 articles were selected for analysis. The majority of the analysed articles were theoretical reviews. The concept of resilience in Psychoanalysis tends to be related to other concepts (e.g. trauma and violence). By itself it indicates an ability that was built fundamentally in through relationships: between subjects, and between subjects and their environments. The studies agree on the notion of resilience as a process that goes beyond simple adaptation. It is in fact an ability to survive, related to intra-psychic capabilities and early emotional experiences. In this respect, resilience emerges as a characteristic that is closely related to the social context of the subject. In fact, it develops from and within this context. ***Resiliência e psicanálise: uma revisão sistemática*** O objetivo deste trabalho foi investigar o conceito de resiliência estudando textos publicados no campo da psicanálise (em um período de dez anos). Através de uma revisão sistemática de artigos publicados entre 2004 e 2014, usando descritores em português, espanhol e inglês. Foram pesquisadas cinco bases de dados: Pubmed, Lilacs, Scielo, BVS Index Psi e PsycInfo. Reunimos 280 artigos publicados, incluindo artigos, artigos, revisões e outros tipos de material. Após os critérios de exclusão, 11 artigos foram selecionados para análise. A maioria dos artigos analisados foram revisões teóricas. O conceito de resiliência na psicanálise tende a estar relacionado a outros conceitos (por exemplo, trauma e violência). Por si só indica uma habilidade que foi construída fundamentalmente através de relacionamentos: entre sujeitos e entre sujeitos e seus ambientes. Os estudos concordam com a noção de resiliência como um processo que vai além da simples adaptação. Na verdade, é a capacidade de sobreviver, relacionado às capacidades intra-psíquicas e às experiências emocionais iniciais. A este respeito, a resiliência surge como uma característica intimamente relacionada com o contexto social do sujeito. Na verdade, ela se desenvolve a partir de e dentro desse contexto.